Design a fuel cell based drive dc motor for an electric vehicle applications - M. T. Ibraheem Alnaib, Ahmed; S. Sultan, Nashwan; T. Mahmood, Omar (International Journal of Engineering and Technology, 2018)
The Applications of a Fuel cell (FC) in the field of the electric vehicle has realized wide popularity since the past few years because of the problem of relative increases in fossil fuel prices in addition to depletion of this fuel. The objective of this study is to design DC drivers based on DC-DC buck converter for separately excited DC motor as a traction motor used for an electric vehicle. This motor is fed by Polymer Electrolyte Membrane (PEM) FC as a renewable energy source. Many control strategies are implemented to produce the suitable gating signal for the buck converter and get the best motor operation response which where Proportional Integral (PI) controller, Fuzzy Logic (FL) controller, and FL based self-tuning PI controller. The proposed FC power system is modeled and simulated using Matlab-Simulink and Fuzzy toolbox. The performance and accuracy of the proposed algorithm have been investigated in different situations. The simulation results showed that the speed response of the DC motor controlled by the FL based self-tuning PI controller had improved the performance (overshoot, rising time, settling time and steady-state error) when compared to the typical PI controller, and FL controller.Â Â